PENGARUH PROFITABILITAS, NON-DEBT TAX SHIELD DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Joundri Wahyu; Mardanung Patmo Cahjono; Endang Satyawati (Bussman Journal : Indonesian Journal of Business and Management, 2022)
The purpose of this research is to empirically examine the effect of the variables obtained in this study. Profitability, Non Debt Tax Shield, and Company Size on Capital Structure in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2016-2020. The population used in this study is 30 food and beverage companies listed on the Indonesia Stock Exchange for the period 2016-2020. The sampling technique used is purposive sampling  in order to obtain a sample of 18 companies. The results of the research analysis show that partially Profitability has a positive and significant effect on Capital Structure, Non Debt Tax Shieldhas a negative and significant effect on Capital Structure, and Company Size has a significant and negative effect on Capital Structure. Simultaneously the variables of Profitability, Non Debt Tax Shield, and Company Size have a significant effect on Capital Structure (DER). The results of the calculation of the coefficient of determination show that the effect of the independent variable on the dependent variable is 13.5% while the remaining 86.5% is influenced by other variables outside this study